STIGMA SOSIAL TERHADAP NARAPIDANA PEREMPUAN MENYUSUI DAN DAMPAKNYA TERHADAP KESEHATAN MENTAL - Subroto, Mitro; Sabami, Reynalin (Ensiklopedia of Journal, 2024)
This study explores the social stigma faced by incarcerated women who are breastfeeding and its impact on their mental health. The urgency of this research arises from the limited understanding of how societal perceptions affect the well-being of these mothers and their infants. A qualitative approach was employed, utilizing interviews with incarcerated women to gather insights into their experiences. Findings reveal that social stigma significantly contributes to feelings of isolation and anxiety among breastfeeding mothers, adversely affecting their mental health. These results underscore the necessity for improved support systems within correctional facilities to address both breastfeeding and mental health needs.Keywords: social stigma; incarcerated women; breastfeeding; mental health; support systems.